2021
DOI: 10.1200/jco.2021.39.15_suppl.4102
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of sorafenib, lenvatinib, and nivolumab as first-line systemic therapy for patients with advanced hepatocellular carcinoma and Child-Pugh class B cirrhosis treated at VA Medical Centers.

Abstract: 4102 Background: Up to 90% of cases of hepatocellular carcinoma (HCC) in the U.S. occur in patients with cirrhosis. As prognosis in patients with decompensated cirrhosis may be more related to liver function than tumor stage, patients with Child-Pugh (CP) class B and C cirrhosis are often excluded from randomized trials despite representing up to 30% of patients treated with systemic therapy in clinical practice. While prospective data such as the GIDEON registry and CHECKMATE-040 have demonstrated safety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Thereafter, 21 articles were excluded and 15 studies were finally included for meta-analysis (1 clinical trial and 14 observational studies), [13,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] 4 of these being abstracts. [25][26][27][28] Between reviewer agreement for the inclusion process was 0.75 (95% CI, 0.70-0.80), as assessed by the kappa coefficient. There was disagreement with respect to 4 studies and it was resolved by a third reviewer (M.R.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thereafter, 21 articles were excluded and 15 studies were finally included for meta-analysis (1 clinical trial and 14 observational studies), [13,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] 4 of these being abstracts. [25][26][27][28] Between reviewer agreement for the inclusion process was 0.75 (95% CI, 0.70-0.80), as assessed by the kappa coefficient. There was disagreement with respect to 4 studies and it was resolved by a third reviewer (M.R.…”
Section: Resultsmentioning
confidence: 99%
“…[32][33][34] In total, 639 (27.7%) patients were classified as Child-Pugh B and 34 (1.5%) as Child-Pugh C. [27,29,31,33,35] Three of the studies included only Child-Pugh B patients [13,26,30] and 1 study included Child-Pugh B and C patients only. [27] Patients Child-Pugh B and C patients The treatment line was described in 319 patients (47.1%), [13,23,[26][27][28]30,36] of which 212 patients (66.5%) were in the first line, 93 (29.2%) in the second line, and 14 (4.9%) in the third line. Only 3 of the 15 studies [13,28,30] reported the BCLC stage in Child-Pugh B or C patients but in none of these studies was the OS analyzed according to the BCLC stage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unclear if this is due to those patients having overall better general fitness or if the treatment was effective in this patient population. Given that clinical trials and provincial drug reimbursement criteria are typically restricted to Child-Pugh A patients, real-world studies of effectiveness of emerging therapies for Child-Pugh B patients, particularly Child-Pugh score B7, should be conducted to determine if clinical outcomes could be improved for those patients and this is currently being explored by several groups (24,25). Finally, we observed that patients with HCV, the most common etiologic risk factor in this study, had better survival than patients with an unknown etiology.…”
Section: Discussionmentioning
confidence: 99%